Modelo de gestión Lean como herramienta para la disminución de desperdicios en los procesos productivos de una cocina. - Vela Chávez, Giovanny Vladimir (2020)
The research aims to establish a model with tools based on the Lean Manufacturing´s philosophy, which can be applied within the productive processes of a kitchen; due to the high percentage of food waste worldwide and the lack of modern management models within the kitchen that help control and manage the resources involved in it. A Lean management model was created to reduce the waste of resources involved in the production of food in a kitchen. To this end, information was collected of the tools and techniques that fit the productive model of the kitchen. The initial state of the kitchen of the Pim's restaurant was evaluated and analyzed, identifying problems in the productive process related to raw materials, human resources and time. In order to solve these problems, three tools were considered, classified in three phases: Diagnosis, Operation and Monitoring, these in turn are composed of the following techniques: Value Stream Mapping (VSM), 5 "S", Jidoka, Standardization and Visual Management.